Association between emotional problems and dizziness by age in a representative population in Korea - Yeon Ran Hong; Hye-Sun Byun; Jin Seub Hwang (Acta Psychologica, 2025)
Objective: Emotional problems like depression and anxiety are closely related to various physical and mental disorders. However, the specific relationship between emotional problems and dizziness is not well understood. The main purpose of this study is to examine the association between emotional problems and dizziness by age in a representative population of Korea. Methods: This study included 672 participants aged 40 and older who had experienced dizziness, based on data from the 2021 Korea National Health and Nutrition Examination Survey [KNHANES]. Participants currently undergoing treatment for stroke, cancer, those with fasting blood sugar levels below 70 mg/dL, and those with anemia were excluded. A multivariate logistic regression analysis was used to calculate the odds ratio [OR] for the occurrence of dizziness, comparing groups with and without anxiety and depression. Interaction between anxiety and age [p = 0.048] was analyzed by stratifying the participants into groups under and over 70 years of age. Results: The prevalence of dizziness among the study participants was 30.65 %. After adjusting for gender, excessive alcohol use, smoking, cervical disc disorders, and sleep duration, it was found that participants with anxiety had a 2.13 times higher likelihood of experiencing dizziness compared to those without anxiety [OR = 2.130, 95 % CI: 1.160–3.912]. Participants with depressive symptoms were 1.86 times more likely to experience dizziness compared to those without depression [OR = 1.86, 95 % CI: 1.003–3.461]. Stratified analysis showed that participants under 70 years with anxiety had a 2.63 times higher likelihood of experiencing dizziness [OR = 2.630, CI: 1.349–5.126]. Conclusion: This study confirms that anxiety and depression significantly impact the occurrence of dizziness, with a stronger effect observed in the population under 70 years old. Focusing on emotional problems such as anxiety and depression may help in managing dizziness, especially in those under 70.